Apolipoprotein A-I positively associated with diabetes in women independently of apolipoprotein E genotype and apolipoprotein B levels - Onat, Altan; Komurcu-Bayrak, Evrim; Can, Gunay; Kucukdurmaz, Zekeriya; Hergenc, Gulay; Erginel-Unaltuna, Nihan (ELSEVIER SCIENCE INC, 2010)
Objective: Given the elevated apolipoprotein (apo) A-I level enhancement of type 2 diabetes among Turks, the interrelation among it, apoB, and apoE genotype with respect to the likelihood of diabetes and metabolic syndrome (MetS), and the role of gender need further investigation. Methods: A random sample of Turkish adults genotyped for apoE with measured serum apoB and apoA-I concentrations was studied cross-sectionally. Apo epsilon 2/epsilon 4 genotype was excluded to avoid confounding. MetS was identified by modified criteria of the Adult Treatment Panel III. Results: Among 1673 participants, epsilon 3 homozygotes prevailed in 74%, apoE2 (epsilon 2/0, epsilon 2/epsilon 2) in 12%, and apoE4 (epsilon 3/epsilon 4. epsilon 4/epsilon 4) in 13%. Low-density lipoprotein cholesterol and apoB levels were significantly lower and apoE concentrations higher in the apoE2 than in the remaining groups. ApoA-I levels in female subjects were significantly higher than in the E4 group. Multivariable analysis for determinants of apoB showed apoE genotype, serum apoE, C-reactive protein, apoA-I, and triacylglycerol levels to be major independent covariates. Logistic regression analyses for MetS, adjusted for potential confounders, revealed that apoB is linked to MetS in men independently of serum triacylglycerols and apoE2 group, whereas that in women in the apoE2 group was associated with MetS by mediation by triacylglycerols or apoB. The independent inverse association of apoA-I with MetS was considered apparent. Multi-adjusted likelihood of diabetes was associated only with triacylglycerol levels and, in women, with apoA-I (odds ratio 1.43, 95% confidence interval 1.10-1.86, per 1 SD increment). Conclusion: The confirmed positive association of serum apoA-I with diabetes in Turkish women is independent of apoE genotype and apoB levels. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Apolipoproteins A-I, B, and E; Apolipoprotein E genotype; Diabetes type 2; Gender difference; Metabolic syndrome; C-REACTIVE PROTEIN; E POLYMORPHISM; RISK; LIPOPROTEINS; DEFINITION; DISEASE; MARKERS; OBESITY; LIPIDS; Nutrition & Dietetics